Redressing urban isolation: A multi-city case study in India - Sameer Ali; Abraham George (Journal of Urban Management, 2022)
Urbanization has brought in expeditious changing world trends from dispersed rural settlements to denser urban centers. Higher frequent economic activities have attracted a large in-flow of job seekers, migrant laborers, and foreign investors to urban centers, furthering the complexity. Contrary to beliefs, urban demography has not brought people together; instead, it has created a new concern, Urban Isolation. The paper tries to explain issues related to urban isolation from examples of cities experiencing it. Results from a survey to determine factors leading to urban isolation for three major cities in India, namely, Mumbai, Kolkata, and Kochi, are also presented. The study includes sensitivity analysis using ANOVA for gender, age group, and household sizes. Factor analysis resulted in two prominent factors, "Sociability" and "Acceptability." The paper provides probable solutions to counter the adverse effects of Urban Isolation. The findings from this study may be highly demographic-centric, catering to the Indian scenario.
Keywords: 710; Community involvement; Social impacts; Social isolation; Urban health; Urban isolation